Gendering Political Party Financing in Nigeria: Evidence from the 2023 General Elections - Babayo Sule; Seroala Tsoeu-Ntokoane; Alouis Chilunjika; Ahmed Lawan (UIN Sunan Gunung Djati, 2025)
The funding of political parties during the electoral process in Nigeria is gradually undermining democratic competition, accountability, transparency and opportunities for the weak and dominated sections of the society. The legal provisions in both the 1999 Constitution and the Electoral Act 2022 unequivocally set out the ceiling on expenditure, description of legal sources of campaign expenditure, ceiling on contributions and associated penalties for violations. Unfortunately, experience, particularly in the 2015, 2019 and 2023 parliamentary elections, has shown excessive spending, breaches of the rules and impunity for violations that were not sanctioned by the relevant authorities. This study therefore examines how the party funding process has disadvantaged and excluded women from participating in elective offices, resulting in an extremely small number of women winning in the recently concluded 2023 general elections. The study is based on a qualitative-descriptive research design. Data was collected through in-depth interviews with informants and focus group discussions as well as personal observation of participants. The data collected was grouped into themes and discussed using tables, charts and empirical analyses. The study reports that women are marginalised, dominated, overshadowed and oppressed by men in Nigerian politics because of men's overspending. The study recommends, among other things, that policies, including harsh penalties, should be applied to offenders who spend beyond the limit in order to control money politics and create a level playing field.